2018
DOI: 10.12688/wellcomeopenres.13373.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performances of the fluorescent spot test for G6PD deficiency in newborns along the Thailand-Myanmar border: A cohort study

Abstract: Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is an inherited enzymatic disorder associated with severe neonatal hyperbilirubinemia and acute haemolysis after exposure to certain drugs or infections. The disorder can be diagnosed phenotypically with a fluorescent spot test (FST), which is a simple test that requires training and basic laboratory equipment. This study aimed to assess the diagnostic performances of the FST used on umbilical cord blood by locally-trained staff and to compare tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 34 publications
(41 reference statements)
2
44
0
Order By: Relevance
“…Since male and female distribution patterns of blood G6PD activity were different, normal G6PD activity reference values for males and females were reported separately. It was shown that bimodal distribution of male G6PD activity was affected by obvious enzymatic deficient values of mutated hemizygous males, whereas normal distribution of female G6PD activity showing wide range of enzymatic activities resulted from lyonization in heterozygous females . After minimizing the impact of severe G6PD deficient activity (below 10% of median value) on the reference normal value by excluding 5 males from spectrophotometric data set, the standardized normal reference values of female and AMM G6PD activity from spectrophotometric and automated UV enzymatic method of a study population were established.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since male and female distribution patterns of blood G6PD activity were different, normal G6PD activity reference values for males and females were reported separately. It was shown that bimodal distribution of male G6PD activity was affected by obvious enzymatic deficient values of mutated hemizygous males, whereas normal distribution of female G6PD activity showing wide range of enzymatic activities resulted from lyonization in heterozygous females . After minimizing the impact of severe G6PD deficient activity (below 10% of median value) on the reference normal value by excluding 5 males from spectrophotometric data set, the standardized normal reference values of female and AMM G6PD activity from spectrophotometric and automated UV enzymatic method of a study population were established.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that bimodal distribution of male G6PD activity was affected by obvious enzymatic deficient values of mutated hemizygous males, whereas normal distribution of female G6PD activity showing wide range of enzymatic activities resulted from lyonization in heterozygous females. 3 After minimizing the impact of severe G6PD deficient activity (below 10% of median value) on the reference normal value by excluding 5 males from spectrophotometric data set, the standardized normal reference values of female and AMM G6PD activity from spectrophotometric and automated UV enzymatic method of a study population were established. The normal reference values of females from both spectrometric and automated UV enzymatic assays are slightly higher than that of males, which was consistent with a previous report.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations